The root transcriptome dynamics reveals new valuable insights in the salt-resilience mechanism of wild grapevine (Vitis vinifera subsp. sylvestris) - Daldoul, Samia; Hanzouli, Faouzia; Hamdi, Zohra; Chenenaoui, Synda; Wetzel, Thierry; Nick, Peter; Mliki, Ahmed; Gargouri, Mahmoud (Frontiers in Plant Science, 2022)
Most of elite cultivated grapevine varieties (Vitis vinifera L.), conventionally grafted on rootstocks, are becoming more and more affected by climate changes, such as increase of salinity. Therefore, we revisited the valuable genetic resources of wild grapevines (V. sylvestris) to elaborate strategies for a sustainable viticulture. Here, we compared physiological and biochemical responses of two salt-tolerant species: a wild grapevine accession “Tebaba” from our previous studies and the conventional rootstock “1103 Paulsen”. Interestingly, our physio-biochemical results showed that under 150mM NaCl, Tebaba maintains higher leaf osmotic potential, lower Na+/ K+ ratio and a significant peaked increase of polyphenol content at the first 8h of salinity stress. This behavior allowed to hypothesis a drastic repatterning of metabolism in Tebaba’s roots following a biphasic response. In order to deepen our understanding on the Tebaba salt tolerance mechanism, we investigated a time-dependent transcriptomic analysis covering three sampling times, 8h, 24h and 48h. The dynamic analysis indicated that Tebaba root cells detect and respond on a large scale within 8h to an accumulation of ROS by enhancing a translational reprogramming process and inducing the transcripts of glycolytic metabolism and flavonoids biosynthesis as a predominate non-enzymatic scavenging process. Afterwards, there is a transition to a largely gluconeogenic stage followed by a combined response mechanism based on cell wall remodeling and lignin biosynthesis with an efficient osmoregulation between 24 and 48 h. This investigation explored for the first time in depth the established cross-talk between the physiological, biochemical and transcriptional regulators contributing to propose a hypothetical model of the dynamic salt mechanism tolerance of wild grapevines. In summary, these findings allowed further understanding of the genetic regulation mechanism of salt-tolerance in V. sylvestris and identified specific candidate genes valuable for appropriate breeding strategies.